Dexamethasone versus betamethasone - a better modality for fetal lung maturity in preterm labour - Aritra Maji; Manisha V Ramani; Vidushi Tiwari (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Prematurity constitutes a serious complication in the field of obstetrics worldwide. Various untoward outcomes like respiratory distress syndrome, intra-ventricular haemorrhage, retinopathy of prematurity, necrotising enterocolitis, low birth weight, neonatal mortality are associated with premature birth. The two common antenatal corticosteroids recommended and widely used for accelerating fetal lung maturity in preterm labour are dexamethasone and betamethasone. Objectives: 1) Comparing efficacy of dexamethasone and betamethasone for fetal lung maturity in preterm infants and 2) To study and compare incidence of other prematurity related complications in both groups. Methodology: This prospective comparative study was done in department of Obstetrics and Gynaecology in MVJ Medical College & Research Hospital involving 100 pregnant lady of gestational age from 28 weeks to 36 weeks + 6 days with preterm labour, who were divided into 2 groups of 50 each. One group was given 4 doses of injection dexamethasone 6mg intramuscularly 12 hours apart while another group was given 2 doses of injection betamethasone 12mg 24 hours apart. The neonates delivered were observed for respiratory distress syndrome, intraventricular haemorrhage, necrotising enterocolitis, low birth weight and neonatal mortality. Result: In our study the neonates who were given dexamethasone prenatally showed lesser evidences of respiratory distress syndrome (30% vs 40%), intraventricular haemorrhage (2% vs 4%), necrotising colitis (2% vs 4%), low birth weight (40% vs 50%) and neonatal deaths (4% vs 8%) as compared to the neonates who received betamethasone before birth. Conclusion: Dexamethasone is superior over betamethasone in reducing adverse neonatal outcomes and more efficacious for preventing neonatal morbidities than betamethasone in pregnant women undergoing preterm deliveries.